2001
DOI: 10.1093/emboj/20.18.5060
|View full text |Cite
|
Sign up to set email alerts
|

Citrin and aralar1 are Ca2+-stimulated aspartate/glutamate transporters in mitochondria

Abstract: The mitochondrial aspartate/glutamate carrier catalyzes an important step in both the urea cycle and the aspartate/malate NADH shuttle. Citrin and aralar1 are homologous proteins belonging to the mitochondrial carrier family with EF-hand Ca 2+ -binding motifs in their N-terminal domains. Both proteins and their C-terminal domains were overexpressed in Escherichia coli, reconstituted into liposomes and shown to catalyze the electrogenic exchange of aspartate for glutamate and a H + . Overexpression of the carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
410
0
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 455 publications
(442 citation statements)
references
References 47 publications
14
410
0
3
Order By: Relevance
“…SLC25A12 encodes the mitochondrial aspartate-glutamate carrier isoform 1 (AGC1). The specific SLC25A12 homozygous mutation identified is c.1058G>A, which results in an Arg353Gln substitution in the 678 amino acid AGC1 protein (Palmieri et al 2001). Moreover, SLC25A12 is located in one of the large regions of homozygosity shared by both affected children that we had demonstrated by genome-wide SNP microarray analysis (Supplemental Table 2).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…SLC25A12 encodes the mitochondrial aspartate-glutamate carrier isoform 1 (AGC1). The specific SLC25A12 homozygous mutation identified is c.1058G>A, which results in an Arg353Gln substitution in the 678 amino acid AGC1 protein (Palmieri et al 2001). Moreover, SLC25A12 is located in one of the large regions of homozygosity shared by both affected children that we had demonstrated by genome-wide SNP microarray analysis (Supplemental Table 2).…”
Section: Resultsmentioning
confidence: 86%
“…Human wild-type and mutant AGC1 proteins were overexpressed as inclusion bodies in the cytosol of Escherichia coli C0214, solubilized, and purified as described (Palmieri et al 2001;Fiermonte et al 2009). The transport activities of the recombinant purified proteins were assayed as described (Palmieri et al 1995(Palmieri et al , 2001). The amount of both wild-type and mutant AGC1 incorporated into liposomes was about 20 % of the protein added to the reconstitution mixture.…”
Section: Methodsmentioning
confidence: 99%
“…In collaboration with two other groups of researchers, we have found that citrin and aralar are isoforms of aspartate glutamate carriers (AGCs) (Palmieri et al 2001). Recombinant citrin and aralar reconstituted into liposomes showed electrogenic exchange of aspartate for glutamate and H ϩ .…”
Section: Citrin and Aralar As Aspartate Glutamate Carriersmentioning
confidence: 94%
“…This gene spreads over about 110 kb and is expressed primarily as 2.9 and 3.2 kb mRNA species, which encode a 678 amino-acid protein that is a calcium-dependent aspartate/glutamate mitochondrial carrier (AGC1). AGC1 plays an important role in the malate/aspartate shuttle, regulating the cytosolic redox state that controls conversion of lactate to pyruvate (Palmieri et al, 2001). We therefore examined whether, in autistic patients, this gene influences an intermediate biochemical phenotype characteristic of mitochondrial dysfunction, defined by plasma lactate levels and lactate/ pyruvate ratio distribution, and hence might play a role in the etiology of autism.…”
Section: Introductionmentioning
confidence: 99%